Why Be Funny: The Influence of Social Norms on the Communicative Functions of Humor - Nathan Miczo; John C. Meyer (Behavioral Sciences)
Humor is a valued social activity and, as such, should be influenced by social norms. This investigation examined the relationships between the functions of humor and the theory of normative social behavior. Descriptive norms are the foundation of TNSB. However, the theory argues that those norms are influenced by a set of moderators that can strengthen or attenuate proposed relationships. One hundred and sixty-three college students completed measures of TNSB variables (descriptive norms, injunctive norms, outcome expectation, group identification, and reward) as well as Ramsey and Meyer’s functions of humor scale (identification, clarification, enforcement, and differentiation). Though descriptive norms significantly correlated with all four humor functions, in regression analyses, no significant associations emerged. On the other hand, injunctive norms consistently predicted humor functions. In moderation analyses, the interaction between descriptive norms and reward was significant for all four functions of humor. The discussion highlights the role that normative mechanisms play in shaping the ways people use humor in their everyday lives.